Historical dictionary of the Chechen conflict - Askerov, Ali (Historical dictionaries of war, revolution, and civil unrest., 2015)
Covers the history of the Chechen conflict through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 500 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture.